Bayesian Analysis of Time‐Series Data under Case‐Crossover Designs: Posterior Equivalence and Inference. Issue 4 (29th November 2013) - Li, Shi; Mukherjee, Bhramar; Batterman, Stuart; Ghosh, Malay
Summary Case‐crossover designs are widely used to study short‐term exposure effects on the risk of acute adverse health events. While the frequentist literature on this topic is vast, there is no Bayesian work in this general area. The contribution of this paper is twofold. First, the paper establishes Bayesian equivalence results that require characterization of the set of priors under which the posterior distributions of the risk ratio parameters based on a case‐crossover and time‐series analysis are identical. Second, the paper studies inferential issues under case‐crossover designs in a Bayesian framework. Traditionally, a conditional logistic regression is used for inference on risk‐ratio parameters in case‐crossover studies. We consider instead a more general full likelihood‐based approach which makes less restrictive assumptions on the risk functions. Formulation of a full likelihood leads to growth in the number of parameters proportional to the sample size. We propose a semi‐parametric Bayesian approach using a Dirichlet process prior to handle the random nuisance parameters that appear in a full likelihood formulation. We carry out a simulation study to compare the Bayesian methods based on full and conditional likelihood with the standard frequentist approaches for case‐crossover and time‐series analysis. The proposed methods are illustrated through the Detroit Asthma Morbidity, Air Quality and Traffic study, which examines the association between acute asthma risk and ambient air pollutant concentrations.